Analisis Akuntansi Pajak Penghasilan Badan Pada CV.RTY: Pajak Penghasilan Badan - wita, Wita Widiyanti; Sartika, Novira (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
Every year after the tax year ends, taxpayers will fulfill their obligations to fill out and submit the annual Corporate Income Tax Return (SPT) which is a means for taxpayers to report as well as calculate and determine the amount of income tax payable in the tax year concerned, in this case tax reporting is often not done properly by taxpayers. The purpose of this research is to analyze the application of income tax accounting at CV. RTY whether it is in accordance with the Income Tax Law. This research is descriptive research using a descriptive qualitative and descriptive quantitative approach. Research data obtained from CV. RTY with data collection techniques through interviews and documentation. From the results of the study, it is known that the company in preparing the profit/loss statement is not in accordance with the Income Tax Law so that reconciliation is carried out first and in reporting the company's Annual Tax Return several times delaying or missing the reporting date. Different from previous studies, in this study researchers calculated the amount of tax credit paid by CV. RTY not through the Annual SPT but using SSP PPh article 25 data in 2023 which is based on the Income Tax Law.